AGROINDUSTRI PENGOLAHAN TANAMAN PANGAN DI KECAMATAN PONJONG KABUPATEN GUNUNG KIDUL - Ken Suratinah; Pinjung Nawang Sari; Nurina Sofiana; Radita Dwi Rahmi; Yogi Pradeksa (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2014)
This research was purposed to  know: 1) the properness of agroindustries utilize  local  crops  as  raw  materials,  2) The  added  value  and  profit  of  agroindustry utilize  the  local  crops  as  raw  materials,  3)  The  poverty  and  prosperity  level  of farmer’s  households  in  the  research  area.  The  kind  of  crops  that  researched  are paddy,  corn,  soya  beans,  ground  nuts,  and  cassava.  This  research  located  in  two villages,  Bedoyo  village  and  Sumbergiri  village,  Kecamatan  Ponjong,  Kabupaten Gunung  Kidul,  Regency  of  Yogyakarta.  The  used  basic  method  was  analytic descriptive, with purposive approach to choose samples of the 90 farmer households which  have  crops  fields  and  agroindustries.  From  the  data  analysis  we  can  inform that:  1)  Agroindustry  using  cassava,  corn,  soya  beans,  and  ground  nuts  as  raw materials were profitable and could absorb a lot of labors around the environtment with range of /C ratio betw een 1,13 –  186,17%, 2) Agroindustry using paddy as raw material  was  not  profitable  and  ineffecient  because  its  taking  too  much  labor,  3) Average incomes of farmers about Rp 10.502.202/year and they are not in poverty, 4) Food  agroindustries  contribute  to  farmer’s  income  about  Rp  14.021.262/year.  It draws a  conclussion food agroindustries have lots of adventages 1) help increasing farmer’s income 2) absorb labor from the environtment, 3) with grow the industries scale can increasing farmer’s skills and prosperity.  Penelitian ini bertujuanuntuk mengetahui: 1) kelayakan, 2) nilai tambahdankeuntungan, 3) kemiskinandan kesejahteraanrumah tanggapetaniagroindustripengolahtanamanlokalsebagai bahan baku.Jenistanamanyangditelitiadalahpadi, jagung, kedelai,kacang tanah, danketela pohon. Penelitian dilakukan diDesaBedoyodanSumbergiri,KecamatanPonjong, Gunungkidul. Menggunakan metodedasaranalitikdeskriptif,dengan purposivesampling 90rumah tangga petaniyangmengusahakan tanamanpangandan agroindustrinya. Hasil analisis menunjukkanbahwa: 1) agroindustriberbahan baku ketela pohon, jagung, kedelai, dan kacang tanah menguntungkan danmampu menyerap banyak tenaga kerja (/Cantara1,13-186,17%), 2) agroindustriberbahan baku padi tidak menguntungkan dan tidak efisien karena mengambil terlalubanyak tenaga kerja, 3) pendapatan rata-rata rumah tangga tani Rp10.502.202/tahundan tergolong tidak miskin, 4) agro industri pangan berkontribusi terhadap pendapatanrumah tangga rata-rata sebesar Rp14.021.262/tahun. Kesimpulannya, agroindustripangan memiliki banyak keuntungan, yaitu: 1) meningkatkan pendapatan 2) menyeraptenaga kerja, 3) meningkatkan kesejahteraan petani.